Improvement of Agricultural Extension services in European countries - Food and Agriculture Organization of the United Nations. Agriculture Division (Rome : Food and Agriculture Organization of the United Nations, 1954)
This report outlines detailed techniques that have been found useful in stimulating the development extension work in European countries over the years.
lje 04/07/17
Loans
Keywords: Maunder, A. H; Agricultural extension; Agricultural extension-Europe